2016
DOI: 10.1111/bph.13567
|View full text |Cite
|
Sign up to set email alerts
|

The effect of imiquimod on taste bud calcium transients and transmitter secretion

Abstract: Our results provide evidence that there is a subset of taste cells equipped with a range of intracellular mechanisms that respond to imiquimod. The findings are also consistent with a role of imiquimod as an immune response modifier, which shapes peripheral taste responses via 5-HT signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 67 publications
(143 reference statements)
1
13
0
Order By: Relevance
“…Huang et al, ). The average baseline (resting) Ca 2+ of taste cells in these experiments was 160 ± 42 nM ( n = 39 cells), which corresponds well with values reported previously (Huang et al, ; Huang and Wu, ; ). Our criteria for accepting Ca 2+ responses for analysis are described fully in the previous publications (Huang et al, ; Huang and Wu, ).…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…Huang et al, ). The average baseline (resting) Ca 2+ of taste cells in these experiments was 160 ± 42 nM ( n = 39 cells), which corresponds well with values reported previously (Huang et al, ; Huang and Wu, ; ). Our criteria for accepting Ca 2+ responses for analysis are described fully in the previous publications (Huang et al, ; Huang and Wu, ).…”
Section: Methodssupporting
confidence: 91%
“…We hypothesize that GABA evoked by SP mediates inhibitory interactions within the taste bud during gustatory stimulation. Previous studies showed that taste stimulation elicits ATP release from intact taste buds isolated from lingual epithelium (Huang et al, ; ; Murata et al, ; Dvoryanchikov et al, ; Huang and Wu, ; ). ATP is believed to be an important excitatory transmitter between taste buds and gustatory sensory afferent fibres (Finger et al, ; Huang et al, ; Vandenbeuch et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations